Peran Ayah sebagai Pendidik dalam Pendidikan Anak pada Channel Youtube Parenting Rumah Keluarga Risman - Andriani, Putri; Muliati, Indah (Prodi Pendidikan Keagamaan Islam, 2024)
The father is the leader of the family, and is therefore responsible for the lives of his wife and children. The family's goals depend on the father's leadership. Fathers are also model educators for their children. But in reality, the role of fathers as educators has been transformed, even though fathers should be involved in children's education. One of the parenting Youtube channels is “Risman Family Home Parenting.” which discusses the role of fathers in children's education. This study aims to determine the role of fathers as educators in children's education contained in the Youtube channel Parenting Rumah Keluarga Risman. This research uses a qualitative method with a content analysis approach. Data collection was carried out by means of observation and documentation from data sources as many as 3 videos. The results of this study indicate that the role of fathers as educators in children's education contained in the Youtube channel Parenting Rumah Keluarga Risman includes advising children, educating children, educating monotheism, giving wills, tough and independent role models, and providing role models.